THE STUDY OF ELECTROMAGNETIC SITUATION AT THE CIVIL AVIATION AIRPORTS AND FORMATION OF IMPROVEMENT MEASURES - Козловський, Валерій Валерійович; Ходаковський, Олексій Володимирович; Тихенко, Оксана Миколаївна; Куцак, Анастасія Сергіївна (Science-based technologies, 2019)
The research has demonstrated that one of the physical factors of anthropogenic origin, generated by stationary aerodrome objects, is the broad-spectrum electromagnetic fields. They are created due to the operation of outdated radio equipment intended for aircraft maintenance, long service life, and lack of modern navigation instruments. The purpose of the work is to develop the recommendations for the definition of sanitary protection zones and their maintenance at the regulatory level, on the basis of field measurements of the electromagnetic fields intensity levels at the territory of civil aviation facilities. The analysis of field measurements of the electromagnetic levels fields parameters, performed with the help of calibrated voltage meter of electric and magnetic fields P3-31 in accordance with the instruction manual, at the territory of the Odessa International Airport has been carried out. The maximum measurement error did not exceed 2.7 dB. The deviations of terminological and even methodological character in the current standards for electromagnetic safety of Ukraine have been revealed. It is established that the methods of calculating the integral electromagnetic pressure have to be specified, provided that different sources influence the electromagnetic environment. The unit of measurement of the parameters of electric, magnetic and electromagnetic fields must be specified and amended, taking into account the available and perspective list of measuring equipment. Recommendations for the establishment of sanitary protection zones have been developed. It is proved that the existing residential area is out of the boundaries of the sanitary protection zones and zones of construction restriction for the sources of electromagnetic energy radiation at the territory of Odessa airport. The general recommendations for the improvement of electromagnetic environment at the territories of civil aviation aerodrome and its maintenance at the standart level are substantiated.